Naturally occurring acquired primary hypothyroidism in a cat due to lymphocytic thyroiditis. Issue 1 (8th February 2016) - Kent, Andrew; Constantino‐Casas, Fernando; Herrtage, Michael E
Abstract : A five‐year‐old ovariohysterectomised female Bengal cat was presented for investigation of weight gain, despite dietary modification, and a dry, poor quality hair coat with diffuse scaling of the skin. Initial blood testing identified a mild, non‐regenerative anaemia, a mild elevation in serum creatinine concentration and a low serum total thyroxine (T4) concentration. Further thyroid testing also demonstrated low free T4 and elevated serum thyroid‐stimulating hormone concentrations, consistent with a diagnosis of hypothyroidism. The cat was treated with levothyroxine and had a good clinical response, with post‐treatment T4 concentration in the reference interval. The cat was euthanased for an unrelated condition (tracheal lymphoma) six months later, which provided the opportunity for histopathological examination of the thyroid gland. Histopathology was consistent with a bilateral lymphocytic, plasmacytic and neutrophilic thyroiditis. Although rare, naturally occurring acquired hypothyroidism, due to lymphocytic thyroiditis, should be considered as a differential for thyroid dysfunction in cats.